PERLINDUNGAN HUKUM BAGI KONSUMEN PENGGUNA JASA BIRO PERJALANAN WISATA DI YOGYAKARTA YANG MENGALAMI KERUGIAN MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Tri Ananda Caesaryan Dasril; Jeane Neltje Saly (Jurnal Hukum Adigama, 2021)
This study aims to analyze the legal protection of consumers who use travel agency services in the city of Yogyakarta both normatively and empirically and to analyze the responsibilities of travel agency business actors for the fulfillment of the rightsof consumers who use their services in the city of Yogyakarta. The problems studied in this study are how the legal protection of consumers who use travel agency services in the city of Yogyakarta both normatively and empirically and how the responsibility of travel agency business actors for the fulfillment of the rights of consumers of their service users in the city of Yogyakarta. This research is a normative juridical research. The procedure used to solve the problem is to first examine the existing secondary data and then proceed with research on primary data in the field. Data was collected by means of library studies and interviews. Theapproach method used is the statutory approach. The research data after being analyzed using descriptive qualitative methods, the results obtained that the legal protection of consumers who use travel agency services in the city of Yogyakarta isnormatively adequate. This is shown from the provisions as regulated both in Law Number 8 of 1999 concerning Consumer Protection and Law Number 10 of 2009 concerning Tourism. Empirically, consumers who use travel agency services in the city of Yogyakarta have not been fully protected. This is shown from the results of the study that not all travel agencies make agreements that contain the rights and obligations of the parties during the tour. The responsibility of travel agency business actors for the fulfillment of the rights of consumers who use their servicesin the city of Yogyakarta..